What's holding you back? : ten bold steps that define gutsy leaders - Herbold, Robert J. (San Francisco : Jossey-Bass, 2011)
'Quit hiding from tough decisions and learn to confront them head-on Why do managers at all levels sacrifice corporate success by shying away from making the tough decisions? What's Holding You Back? reveals exactly why managers often hesitate to confront difficult issues-whether it's the absence of a perfect solution, the knowledge that no decision will please everyone, etc.-and, most importantly, how they can overcome these common managerial obstacles to maximize their company's success. What's Holding You Back? elucidates the ten core principles of confident leadership, outlining proven tactics by which managers can confront their inner wimp and highlight their inner courage. Features dynamic real-world examples from Apple, Microsoft, Porsche, IBM, Merck, Canon, Sony, Whirlpool, IDEO, Tesco, P&G, Target, 3M, and more Pinpoints the corporate failures that can result from hesitant or self-conscious organizations, and what managers can do to avoid them Clearly delineates how managers can cultivate and deliver accountable and decisive leadership, even during the toughest dilemmas What's Holding You Back? proves that practicing gutsy leadership is the key to operational and innovative excellence in the workplace.'--
Includes bibliographical references (p. 189-201) and index.
Keywords: Decision making; Leadership